To solve the problem shown above you must apply the following proccedure:
1. You have the following function given in the problem:
<span> f(x)=x3–3x–2
2. When you give values to the x and plot each point obtained, you obtain the graph shown in the figure attached.
3. Based on the graph and analizing the alternate form:
f(x)=(x-2)(x+1)</span>²
As you can see, there is two roots x=-1, then, you can conclude that the correct answer is the option b, which is:
b) -1<span>
</span>
Answer:
x = (-5 ± 2√10) / 3
Step-by-step explanation:
5 − 10x − 3x² = 0
Write in standard form:
-3x² − 10x + 5 = 0
Solve with quadratic formula:
x = [ -b ± √(b² − 4ac) ] / 2a
x = [ -(-10) ± √((-10)² − 4(-3)(5)) ] / 2(-3)
x = [ 10 ± √(100 + 60) ] / -6
x = (10 ± 4√10) / -6
x = (-5 ± 2√10) / 3
<u>Answer</u>
C. 39.71
<u>Explanation</u>
33 = p - 6.71
The first step is to make the like terms to be on the same side.
Add 6.71 on both sides of the eqution
33 + 6.71 = p - 6.71 + 6.71
39.71 = p
∴ p = 39.71
The train traveled 60 miles per hour since 360 miles divided by 6 hours gives you 60 mph
D, y-y1=m(x-x1)
^^^^^^^^^^^^^^^